Christology, controversy, and community : New Testament essays in honour of David R. Catchpole - Catchpole, David R.; Horrell, David G.; Tuckett, C. M. (Christopher Mark) (Supplements to Novum Testamentum, 2000)
This collection of essays by an international team of New Testament scholars is in honour of David Catchpole, formerly the Saint Luke's Foundation Professor of Theological Studies at the University of Exeter. The essays represent a range of approaches and topics, connected together by a focus on various kinds of christological claim, whether by the historical Jesus, in the Q tradition, John, Paul or the synoptics, and their connection with controversy and the construction of early Christian community. The contributors are as follows: Stephen Barton, Richard Burridge, Marinus de Jonge, James Du.